Comparison of the Effectiveness of Kencur Warm Water Soaking with Salt Warm Water Against Leg Edema of Third Trimester Pregnant Women in the Working Area of Rawang Health Center, Indonesia - Aprianti, Riri; Sintia Hikma Oktavia (Eureka Herba Indonesia, 2024)
Leg edema is a common complaint in third trimester pregnant women. It is believed that soaking in kencur warm water and salt warm water can help overcome this. Comparing the effectiveness of soaking in warm kencur water with warm salt water on leg edema in third trimester pregnant women. Quasi-experimental research with a pretest-posttest design with the control group. A total of 60 third trimester pregnant women were divided into two groups: the kencur warm water immersion group (n=30) and the salt warm water immersion group (n=30). The intervention was carried out for 15 minutes, twice a day for 3 days. Leg edema was measured using a measuring tape before and after the intervention. There was a significant reduction in leg edema in both groups after intervention (p<0.05). The reduction in leg edema in the kencur warm water immersion group was greater than in the salt warm water immersion group (p<0.05). Kencur warm water soaks are more effective than salt warm water soaks in reducing leg edema in third-trimester pregnant women.